2002
DOI: 10.1124/jpet.300.1.57
|View full text |Cite
|
Sign up to set email alerts
|

[Arg14,Lys15]Nociceptin, a Highly Potent Agonist of the Nociceptin/Orphanin FQ Receptor: in Vitro and in Vivo Studies

Abstract: Nociceptin (NC)/orphanin FQ is the endogenous ligand of a seven-transmembrane domain G protein-coupled receptor, referred to as OP 4 . NC and the OP 4 receptor are structurally related to opioid peptides and receptors; however, NC does not interact with classical opioid receptors, and the OP 4 receptor does not bind any selective opioid receptor ligand (for recent reviews, see Calo' et al., 2000c;Meunier, 2000). It has been demonstrated that NC modulates several biological functions, including pain threshold, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
42
0

Year Published

2002
2002
2018
2018

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 50 publications
(46 citation statements)
references
References 38 publications
4
42
0
Order By: Relevance
“…Okada et al (2000) inserted Arg-Lys at different positions throughout the peptide, leading to the identification of [Arg 14 Lys 15 ]N/OFQ as a highly potent NOP full agonist approximately 10-fold more potent than N/OFQ (Rizzi et al, 2002c). Similar results were obtained in different laboratories in various bioassay and other cellular studies (Rizzi et al, 2002c;Basso et al, 2005;Trombella et al, 2005 (Rizzi et al, 2002c).…”
Section: A Nociceptin/orphanin Fq Related Peptidessupporting
confidence: 68%
See 1 more Smart Citation
“…Okada et al (2000) inserted Arg-Lys at different positions throughout the peptide, leading to the identification of [Arg 14 Lys 15 ]N/OFQ as a highly potent NOP full agonist approximately 10-fold more potent than N/OFQ (Rizzi et al, 2002c). Similar results were obtained in different laboratories in various bioassay and other cellular studies (Rizzi et al, 2002c;Basso et al, 2005;Trombella et al, 2005 (Rizzi et al, 2002c).…”
Section: A Nociceptin/orphanin Fq Related Peptidessupporting
confidence: 68%
“…Interestingly, when measuring calcium mobilization in cells expressing chimeric G-proteins , the potency of ZP120 was relatively low, as was the case with several other NOP ligands such as UFP-112, UFP-113, and PWT2-N/OFQ (see Table 2). Each of these compounds is characterized by a slow kinetics of activation of the NOP receptor, as suggested by bioassay experiments in isolated tissues (Rizzi et al, 2002c;Calo' et al, 2011;Guerrini et al, 2014). It is possible that the rapid kinetics that characterize the calcium transient response may be incompatible with the slow kinetics of the ligand receptor interaction (for a detailed discussion of this topic see Camarda et al, 2009;Rizzi et al, 2014).…”
Section: B Nociceptin/orphanin Fq Unrelated Peptidesmentioning
confidence: 99%
“…Indeed, we found that intracerebroventricular infusions of an OFQ agonist significantly reduced the frequency of LH pulses in both intact luteal phase and OVX ewes. Although these inhibitory effects were observed with an agonist, there is strong evidence that this OFQ analog interacts with the ORL-1 and not the classical opioid receptors (41). In light of this specificity and evidence that OFQ is the endogenous ligand for the ORL-1 receptor (1), these data provide in vivo evidence for a role of OFQ in regulation of the ovine reproductive neuroendocrine system.…”
Section: Discussionmentioning
confidence: 76%
“…In all these assays, UFP-102 displayed higher potency than the natural peptide (between 10-and 100-fold) and produced slow onset but longer lasting effects. These kinetic features of UFP-102, also revealed by the in vitro experiments, may be attributed to a slower but stronger binding to the NOP receptor compared with N/OFQ; at least in part, they may due also to a decrease susceptibility of UFP-102 to degradation by peptidases, a feature that may be conferred to the molecule by the presence, toward the C terminus, of the cationic residues Arg 14 ,Lys 15 (Rizzi et al, 2002c). The high selectivity of action of UFP-102 was also confirmed in vivo in mice.…”
Section: Discussionmentioning
confidence: 94%